(untitled) (Research, Society and Development, 2023)
The aim of the study was to evaluate the effect of the dry needling technique associated with electrostimulation in students with migraine. It was an interventionist study, with a quantitative approach, carried out at the physiotherapy sector of the University of Fortaleza. Five students were submitted to the protocol. The first stage consisted of a physical assessment and completion of questionnaires. The second stage contemplated the intervention where the needles were positioned in the homeostatic point, in the frontal muscle on the headache side and bilaterally in the anterior temporal. The parameters used were: frequency 80Hz, pulse width 60μs, for 20 minutes with the effect variation of intensity and frequency. Ten appointments took place. Of the participants, 80% were female, 60% used electronic devices for 7 to 8 hours a day, 60% reported suffering from anxiety, 60% considered having sleep disorders. Regarding migraine, 60% reported moderate to severe pain, 60% stated that the episodes lasted up to 4 hours even when using medication, 100% classified the pain as pulsatile. After reassessment, there was an improvement in the mean values on palpation of the muscles: right anterior temporal, bilateral anterior and posterior scalene, left middle scalene and bilateral upper trapezius fibers. In other muscles, the average remained the same. Cervical range of motion improved for left flexion, extension and rotation. Therefore, it was possible to verify that the effect of dry needling associated with electrical stimulation was not effective in the treatment of migraine-type headache.